The children rights protection in the new normal era: an Indonesia experience during covid-19 pandemic - Izza Aliyatul Millah; Pujiyono Pujiyono (Legality : Jurnal Ilmiah Hukum, 2020)
The new normal era is a necessity and must be faced by all countries until the discovery of the Covid-19 disease vaccine. The implementation of this new normal era policy has caused public debate related to various concerns of the people, especially the state’s readiness to guarantee the safety of the population from the transmission of Covid-19, especially in the protection of children in terms of fulfilling their rights. This paper aims to find out child protection providers in providing protection and fulfillment of children’s rights in new normal behavior during the Covid-19 pandemic and to find out the implementation of policies towards the protection of children’s rights in new normal behavior during the Covid-19 pandemic. This research uses doctrinal law research. Legal information sources use primary legal materials (relevant regulations and documents) for further qualitative analysis. The approach used is a statutory approach and conceptual approach in helping solving problem formulations. This research concludes that the right effort to deal with the new normal era is to strengthen child protection based on children’s rights, starting from parents, family, community, and government during the pandemic. Associated with the establishment of a policy schedule for children entering school when the new normal era in the Covid-19 pandemic. The key to protecting children in the new normal era is the health protocol rules that can be a guideline for parents and caregivers of children and the fulfillment of children’s primary rights in the new normal era is the health and safety aspects of children.